Sharia Cooperatives as an Inclusive and Ethical Financial Alternative for Economic Development - Citrasari, Andi Tenri (PINISI Discretion Review, 2024)
Sharia cooperatives are economic institutions based on Islamic law that prioritize justice, mutual benefit, and balance in all their activities. These cooperatives operate under the fundamental principles of fairness and transparency, ensuring that financial transactions comply with Islamic ethical standards. The main principles of the sharia cooperative system include the non-riba (interest-free) principle, avoiding speculation (gharar), and ensuring that every transaction is conducted by sharia provisions. This system fosters ethical economic activities that emphasize real asset-based transactions and risk-sharing mechanisms. Members of a sharia cooperative not only use the services but also become owners, actively participating in decision-making processes and sharing profits and risks. This is in line with the principles of musyarakah (cooperation) and mudharabah (profit-sharing), which encourage collective welfare rather than individual gains. Therefore, sharia cooperatives offer a sustainable and inclusive financial alternative that aligns with religious values while addressing economic needs. Sharia cooperatives play a crucial role in providing financial access to underserved communities, particularly those who are unable to obtain financing from conventional financial institutions due to interest-based constraints. By offering fair and just financial solutions, sharia cooperatives empower individuals to improve their economic conditions. Additionally, these cooperatives contribute to economic development by encouraging entrepreneurship, fostering the growth of new businesses, and supporting social welfare programs.